Faktor Yang Mempengaruhi Tingkat Ketahanan Pangan Desa (Studi Kasus di Kabupaten Malang) - Lien Damayanti (Universitas Tadulako, 2007)
This research aims (1) to analysis factors affecting the level of food tenacity both directly and indirectly, (2) to analysis the correlation and the influence between availability, food access and livelihood, nutrition and health, and food susceptibility, and (3) to analysis the effect of availability, food access and livelihood, nutrition and health, and food susceptibility on the level of food tenacity either partial or combination. This research conducted in 3 sub-district at Malang District: (1) Kepanjen, (2) Pakisaji, and (3) Sumber Pucung with 30 villages. The research carried out using Path analysis with indicators: (1) Availability, (2) Food access and Livelihood, (3) Nutrition and Health, and (4) Food susceptibility. The results of analysis show that only 3 factors significantly affect the level of food tenacity such as food access and livelihood, nutrition and health, and food susceptibility. However, indicator of availability shown no significant. The Successful of food security can be achieved if food could reach to household level.